Unusual Necrotizing Encephalitis in Raccoons and Skunks Concurrently Infected With Canine Distemper Virus and Sarcocystis sp. (May 2016) - Kubiski, S. V.; Sisó, S.; Church, M. E.; Cartoceti, A. N.; Barr, B.; Pesavento, P. A.
Canine distemper virus commonly infects free-ranging, terrestrial mesopredators throughout the United States. Due to the immunosuppressive effects of the virus, concurrent opportunistic infections are also common. Among these, secondary systemic protozoal infections have been described in a number of species. We report an unusual presentation of necrotizing encephalitis associated with Sarcocystis sp in four raccoons and one skunk concurrently infected with canine distemper virus. Lesions were characterized by variably sized necrotizing cavitations composed of abundant mineral admixed with inflammatory cells and protozoa. Sarcocystis sp was confirmed via immunohistochemistry using a monoclonal antibody to Sarcocystis neurona . The pathologic changes are similar to lesions in human AIDS patients infected with Toxoplasma gondii .